Employment Status, Competency Level and Perceived Skill-Labor Market Demand among Garments and Fashion Technology Graduates - Maloto, Maria Fe (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the employment status, competency levels, and perceived skill–labor market alignment of Garments and Fashion Technology graduates from Bohol Island State University (BISU) Main Campus, Batch 2020–2024. Anchored on Human Capital Theory (Becker, 1964), Constructive Alignment Theory (Biggs & Tang, 2011), Experiential Learning Theory (Kolb, 1984), and employability frameworks (Yorke, 2006), the study utilized a descriptive-correlational research design. Data were collected using a researcher-made questionnaire administered to 82 graduates and 9 employers, and analyzed using frequency, percentage, weighted mean, Chi-square test, Mann–Whitney U test, and Kruskal–Wallis test. Findings revealed that most graduates were employed or self-employed, with many securing jobs within a short period, although a notable proportion worked outside their field and earned entry-level income. Graduates were generally rated as competent, demonstrating strong core garments technology skills and professional or soft skills, while modern and digital skills were identified as the weakest area. Both graduates and employers perceived overall skill–labor market alignment as aligned, particularly in industry requirements and curriculum relevance, though gaps in digital competencies remained evident. No significant relationship was found between competency levels and employment status or time to first job, but competency was significantly related to perceived alignment. No significant differences were observed across demographic variables, while course completed showed a significant relationship with employment status. The study concludes that while the program effectively develops foundational competencies and supports employability, strengthening digital skills is necessary to meet evolving industry demands. It recommends curriculum enhancement, faculty development, improved facilities, stronger industry collaboration, and continuous professional development among graduates. The study aligns with SDG 4 (Quality Education), SDG 8 (Decent Work and Economic Growth), and SDG 9 (Industry, Innovation and Infrastructure) by promoting competency-based education, employability, and technological integration. It contributes to educational, socio-economic, and technological sustainability by supporting curriculum improvement, workforce readiness, and industry-responsive training systems.